The armchair and the trolley: an argument for experimental ethics. - Kahane, Guy (Philosophical Studies, 2013)
Ethical theory often starts with our intuitions about particular cases and tries to uncover the principles that are implicit in them; work on the 'trolley problem' is a paradigmatic example of this approach. But ethicists are no longer the only ones chasing trolleys. In recent years, psychologists and neuroscientists have also turned to study our moral intuitions and what underlies them. The relation between these two inquiries, which investigate similar examples and intuitions, and sometimes produce parallel results, is puzzling. Does it matter to ethics whether its armchair conclusions match the psychologists' findings? I argue that reflection on this question exposes psychological presuppositions implicit in armchair ethical theorising. When these presuppositions are made explicit, it becomes clear that empirical evidence can (and should) play a positive role in ethical theorising. Unlike recent assaults on the armchair, the argument I develop is not driven by a naturalist agenda, or meant to cast doubt on the reliability of our moral intuitions; on the contrary, it is even compatible with non-naturalism, and takes the reliability of intuition as its premise. The argument is rather that if our moral intuitions are reliable, then psychological evidence should play a surprisingly significant role in the justification of moral principles.